Teachers’ school guidance practice toward PISA enhancement: a comparison between Malaysia and Finland - Abdul Wahab, Nurshidah; Amzat, Ismail Hussein; Yusuf, Byabazaire (International Islamic University Malaysia, 2018)
This study aimed to compare Malaysian and Finnish subject teachers’ perceptions of the practice of school guidance. In addition, it is aimed to compare Malaysian and Finnish subject teachers’ perceptions of PISA and its significance and Finnish subject teachers’ perceptions of the school guidance practice towards PISA enhancement. This study is a qualitative research, employing semi-structured interviews with four subject teachers; two participants from Finland and two participants from Malaysia. The study uses a purposive sample and the sample size consists of 4 participants. The selected interviewees are teachers in secondary schools in both countries. The data collected are analysed using three phases of thematic analysis with the help of analysis computer software, Nvivo for a more visible systematic analysis. Teachers have different interpretations of what constitutes school guidance; its meaning, definition, framework. Additionally, the personnel involved in school guidance differs in Malaysia and Finland. In terms of the teaching context, participant teachers in consensus agreed that PISA assessment plays little role in the determination of what they believe is important for their students’ needs (skills) to survive in their life after school. School guidance has the potential to contribute towards PISA enhancement if and when the school guidance programme is financially supported plus a strong support or desire from students, teachers, counsellors and the school administration as a whole.